Bonjour besoin d'aide :)
TITRE ( Application de la factorisation : résolution d'équations )

1. Résoudre IR l'équation :
5 ( x - 2 ) ( 2x + 4 ) - (x² - 4 ) = 0

2.Résoudre IR l'équation :
( 3x - 1 )² - 4 ( 3x - 1 ) =0


Répondre :

Bonjour,

5(x-2)(2x+4)-(x²-4) = 0

⇒ 5(2x²+4x-4x-8)-(x²-4) = 0

⇒ 10x²-40-x²+4 = 0

⇒ 9x²-36=0

⇒ (3x+6)(3x-6)=0

⇒ 3x+6=0 ou 3x-6=0

⇒ 3x=-6 ou 3x=6

⇒ x=-6/3 ou x=6/3

⇒ x=-2  ou x=2

(3x-1)²-4(3x-1)=0

⇒ (3x-1)(3x-1)-4(3x-1)=0

⇒ (3x-1)(3x-1-4)=0

⇒ (3x-1)(3x-5)=0

⇒ 3x-1=0 ou 3x-5=0

⇒ 3x=1 ou 3x=5

⇒ x=1/3 ou x=5/3